Something Special - McPhail, David 1940- (Boston : Joy Street Books, 1988)
Surrounded by parents and siblings with remarkable talents, Sam yearns to be good at something himself, and finds his own special niche when he discovers the pleasures of painting.
Keywords: Individuality -- Fiction; Artists -- Fiction; Family life -- Fiction; Raccoons -- Fiction